Application of regenerative medicine to salivary gland hypofunction - Junichi Tanaka; Kenji Mishima (Elsevier, 2021)
Dry mouth results from hypofunction of the salivary glands due to Sjögren's syndrome (SS), various medications, and radiation therapy for head and neck cancer. In severe cases of salivary gland hypofunction, sialagogues are not always effective due to the loss of salivary parenchyma. Therefore, regenerative medicine using stem cell therapy is a promising treatment for severe cases. Stem cells are classified into three groups: tissue stem cells, embryonic stem cells, and induced pluripotent stem cells. Tissue stem cells, such as hematopoietic stem cells (HSCs), mesenchymal stem cells (MSCs) and salivary stem/progenitor cells, could rescue irradiation-induced salivary gland hypofunction. Both HSCs and MSCs can rescue salivary gland hypofunction through soluble factors in a paracrine manner, while salivary stem/progenitor cells can reconstitute the damaged salivary glands. In fact, we clarified that CD133-positive cells in mouse submandibular glands showed stem cell features, which reconstituted the damaged salivary glands. Furthermore, we focused on the challenge of producing functional salivary glands that are three-dimensionally induced from mouse ES cells.